Measuring HIV and AIDS-related Stigma across South Africa: A Versatile and Multidimensional Scale - Smith, Edward A. (2013)
Reducing HIV and AIDS-related stigma is critical in the fight against HIV/AIDS. Although national campaigns and prevention programs have been implemented across South Africa to address this critical concern (Soul City, 2008; USAIDS, 2007), assessing the impact of these initiatives is difficult as it requires that measurement of HIV/AIDS-related stigma is uniform and comparable nationwide. The appropriateness of existing stigma measures for this task is unclear as measurement of HIV/AIDS related stigma may be qualitatively different across South Africa’s diverse population (Jöreskog, 1971). The current study assesses a theoretically and culturally informed multi-dimensional, HIV/AIDS-related, stigma scale for measurement invariance across a sample drawn from two culturally distinct South African provinces: Limpopo (n = 597) and Western Cape (n = 598). Results suggest measurement invariance across groups for the HIV/AIDS-stigma scale, supporting the scale’s integrity and appropriateness for use across diverse populations.